Relationship between lower limb anthropometry and temporo-spatial parameters in gait of young adults (Relación entre la antropometría de miembro inferior y los parámetros temporo-espaciales en la marcha de adultos jóvenes) - Oscar Valencia; Oscar Araneda; Marcela Cárcamo; Felipe Carpes; Rodrigo Guzmán-Venegas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Temporo-spatial parameters (TSP) are commonly used to characterize human gait. These help to differentiate population groups in different conditions of gait, but can be influenced by lower limb anthropometry. Different strategies are assumed to normalize TSP and permit comparison among people. However, it is not clear how dimensions of the different lower limb segments influence gait TSP. The aim of this study was to verify the relationship between gait TSP and length of the thigh, leg and foot in young adults. The body segments lengths were adjusted for individual height and correlated with gait TSP. We found a correlation between foot length and step width (r = 0.44). When data were adjusted for gender, step time, stride time, cadence and gait speed correlated with foot length in men (r = 0.51, 0.49, -0.49 and -0.43, respectively). Among women, these same TSP correlated only with thigh length (r = 0.43, 0.46, -0.47 and -0.37, respectively). Step and stride length correlated with leg (r = 0.46 and 0.48) and thigh length (r = 0.44 and 0.44) only in men. In conclusion, anthropometric parameters influence TSP differentially for men and women. These data should be considered when studying population groups including people from both genders.